Characterisation of Textile Dye-Degrading Properties of Ligninolytic Fungus Isolate 5-UPM - Khalid, Ariff (2005)
Local white-rot fungi isolated from soil and wood samples were screened for their ability to degrade textile azo dyes. Sixty three white-rot fungi cultures isolated from various Peninsular Malaysia locations in Selangor, Kelantan, Perak and Terengganu were screened for the ability to degrade four textile azo dyes; Ponceau 2R (C.I. 16450), Orange G (C.I. 16230), Direct Blue 71 (C.I. 34140) and Biebrich Scarlet (C.I. 26905). Forty isolates gave positive results with varying degrees of degradation. Based on these results, an unidentified white-rot fungus (Isolate 5-UPM) isolated from Universiti Putra Malaysia (UPM) Selangor campus was selected for further studies due to its ability to completely degrade all four azo dyes in the minimum amount of time. Nutritional studies on defined solid medium showed that Isolate 5- UPM was only able to degrade the four azo dyes under nitrogen-limiting conditions and an additional carbon source such as glucose was needed to provide sufficient energy for the degradation to occur. When grown in two-stage liquid cultures, Isolate 5-UPM was able to degrade 93 to 99 % of 0.2 g/L azo dyes in two to eight days with each dye being degraded at different rates. Direct Blue 71 was degraded the fastest followed by Orange G, Ponceau 2R and Biebrich Scarlet. Generally, azo dye degradation rates were shown to be higher in agitated cultures compared to static cultures, with rates almost twice those in static cultures. Isolate 5-UPM degraded the four azo dyes optimally when incubated at 35 to 45 "C in static cultures. The initial degradation medium (pH 4.5 to 5.9) did not have any significant effects on the degradation rates except for Ponceau 2R cultures where the degradation rate was highest at pH 4.5. However, the final pH of all cultures dropped to approximately pH 4.0. Assays for lignin-modifying enzymes (LMEs) involved in azo dye degradation showed only the presence of laccase (E.C. 1.10.3.2) while lignin peroxidase (E.C. 1.1 1.1.14) and manganese peroxidase (E.C. 1.1 1 .l. 13) were not detected. Laccase activity profile in static liquid degradation cultures showed correlation to the azo dye degradation profile and was highest in cultures incubated at room temperatures except for Biebrich Scarlet cultures, which was highest at 30 "C. The initial pH of the degradation medium (pH 4.5 to 5.9) did not have any significant effect on laccase activity except in Direct Blue 71 culture where it is highest at pH 5.9. Laccase produced by Isolate 5-UPM during azo dye degradation was partially purified and when 2,2'-azinobis (3-ethylbenzothiazoline-6-sulfonate) (ABTS) was used as the substrate, it was shown to have a K,,, value of 0.1 mM, optimum activity at 50 to 70 "C and pH 3.5 to 4.0 while being most stable at room temperature and pH 6.0 to 7.0. Laccase was proven to directly degrade the four azo dyes with the K, values of 1.5 x 10 '3 mM, 9.8 x 10 4 m ~ 1,.8 x 10 4 m an~d 1 .8 x 10 4 m fo~r Po nceau 2R, Orange G, Direct Blue 71 and Biebrich Scarlet, respectively although the latter azo dye inhibited laccase activity at concentrations higher than 0.8 mg/L.